Pengaruh Brand Ambassador Selebriti Korea Selatan terhadap Niat Beli Produk Perawatan Kulit dan Kosmetik yang Dimoderasi Etnosentrisme Konsumen - Sanaji Sanaji; Mafryanda Safinaturrizqy Addiena Shafa (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
The phenomenon of many local skincare and cosmetics companies using South Korean celebrity brand ambassadors has been criticized by netizens because South Korean celebrities are considered not to represent Indonesian skin and can create the perception that